Tyrosine-kinases inhibitors in recurrent platinum-resistant ovarian cancer patients. (January 2016) - Marchetti, C.; Palaia, I.; De Felice, F.; Musella, A.; Donfracesco, C.; Vertechy, L.; Romito, A.; Piacenti, I.; Musio, D.; Muzii, L.; Tombolini, V.; Benedetti Panici, P.
Highlights: The risk of recurrence in ovarian cancer (OC) represents a common entity. The role of tyrosine-kinases inhibitors (TKI) in recurrent OC needs to be clarified. This is the largest reported analysis of published data. This analysis suggests that TKI could be considered a valid option in recurrent OC. Abstract: For many decades, ovarian cancer (OC) has been one of the most common gynecological cancer. Despite advances in OC diagnosis and treatment, the risk of recurrence is ever present and approximately 85% of patients will experience relapse. Recurrent OC after first-line therapy is almost always incurable. Multiple novel therapies, including tyrosine-kinases inhibitors (TKI), have shown promising results, but their role needs to be clarified. In this review we describe the rationale and the clinical evidence regarding the use of TKI for the treatment of recurrent platinum-resistant OC patients.